Israel's attack on Osiraq a model for future preventive strikes - Ford, Peter (USAF Acad., 2005)
Twenty-four years ago, Israeli fighter pilots destroyed the Osiraq nuclear reactor and made a profound statement about global nuclear proliferation. In light of the recent preventive regime change in Iraq, a review of this strike reveals timely lessons for future counterproliferation actions. Using old, new, and primary source evidence, this paper examines Osiraq for lessons from a preventive attack on a non-conventional target. Before attacking Osiraq, Israeli policymakers attempted diplomatic coercion to delay Iraq's nuclear development. Concurrent with diplomatic actions, Israeli planners developed a state-of-the-art military plan to destroy Osiraq. Finally, Israeli leaders weathered the international storm after the strike. The paper examines Israeli decisionmaking for each of these phases. The paper draws two conclusions. First, preventive strikes are valuable primarily for two purposes: buying time and gaining international attention. Second, the strike provided a one-time benefit for Israel. Subsequent strikes will be less effective due to dispersed/hardened nuclear targets and limited intelligence.
Keywords: Geschichte 1981; Nahostkonflikt; Arab-Israeli conflict -- 1973-1993 -- Iraq; Nuclear arms control -- Middle East; Nuclear nonproliferation; Osirak Nuclear Reactor Bombing, Iraq, 1981; Kernkraftwerk; Luftangriff; Irak; Naher Osten; Iraq -- Military relations -- Israel; Israel -- Military relations -- Iraq; Israel; Hochschulschrift